The Problem of Tax Non-Compliance in Paying Taxes in Nunggi Village, Wera District, Bima Regency - Susanto, Dodo (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The level of tax compliance among the people of Nunggi Village appears to be less than satisfactory. Taxpayers have not yet fully embraced the process of paying taxes. This low level of tax awareness ultimately leads to low levels of taxpayer compliance. One of the triggers for this "cultural" lack of tax awareness is the lack of public awareness of taxes. This is what makes the people of Nunggi Village reluctant to pay their taxes on time. Furthermore, law enforcement by these officials remains very weak, making it difficult to build taxpayer trust. The cycle that exists between taxpayer non-compliance and the village government, which has failed to provide information on tax regulations, must be broken immediately. One key to achieving this is through public outreach on tax payments.